Intestinal integrity and performance of broiler chickens fed a probiotic, a prebiotic, or an organic acid - Fernandes, B. C. S. [UNESP] (2014)
This study aimed at evaluating the intestinal integrity, using light and scanning electron microscopy (SEM), and the performance of broiler chickens fed additives alternative to antimicrobials. A total of 1080 male chicks were distributed according to a completely randomized experimental design, with six treatments with six replicates of 30 birds each. The following treatments were evaluated: basal diet (control), basal diet supplemented with an antimicrobial, basal diet supplemented with a probiotic, basal diet supplemented with a prebiotic, basal diet with a symbiotic, and basal diet supplemented with organic acids. Weight gain, feed intake, feed conversion ratio and livability were recorded when broiler chickens were 10, 21, 35, and 42 days old. On day 42, 72 birds were individually weighed and sacrificed. In order to evaluate the morphometrics of the different intestinal wall layers, segments of the small intestine and the cecum were collected from two birds per replicate, and intestinal integrity (SEM) was evaluated in the same segments of two birds per treatment. During the starter period (1-21 days old), birds fed the alternative additives presented similar weight gain as those fed the antimicrobial product, but were not different from control birds. Feed conversion ratio of birds fed alternative additives was better than that of the control birds from one to 10 days of age, but not during the remaining rearing period, and was similar to the birds receiving the antimicrobial. The morphometric parameters of the different intestinal wall layers was not influenced by the treatments. During the total rearing period, the evaluated alternative additives did not improve intestinal integrity or broiler performance.